1993
DOI: 10.1007/bf00282801
|View full text |Cite
|
Sign up to set email alerts
|

The prosomal RNA-binding protein p27K is a member of the α-type human prosomal gene family

Abstract: Monoclonal antibodies demonstrated high conservation during evolution of a prosomal protein of M(r) 27,000 and differentiation--specific expression of the epitope. More than 90% of the reacting antigen was found as a p27K protein in the free messenger ribonucleoprotein (mRNP) fraction but another protein of M(r) 38,000, which shared protease fingerprint patterns with the p27K polypeptide, was also labelled in the nuclear and polyribosomal fractions. Sequencing of cDNA recombinant clones encoding the p27/38K pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Interestingly, proteasomes always appear linked with the free mRNP particles when low salt conditions were used throughout purification (Schmid et al, 1984;Martins de Sa et al, 1986;Nothwang et al, 1992aNothwang et al, , 1992b. In addition, previously we have shown that proteasomes associated in vitro with TMV-RNA and mRNA from adenovirusinfected cells, and Bey et al (1993) have demonstrated that the 27-kDa protein, an α-type subunit of proteasomes, has one distinct mRNA binding domain. A widely accepted argument for a possible relationship among proteasomes and RNA is the presence of small RNA molecules in pure preparations of proteasomes (Arrigo et al, 1985;Martins de Sa et al, 1986).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, proteasomes always appear linked with the free mRNP particles when low salt conditions were used throughout purification (Schmid et al, 1984;Martins de Sa et al, 1986;Nothwang et al, 1992aNothwang et al, , 1992b. In addition, previously we have shown that proteasomes associated in vitro with TMV-RNA and mRNA from adenovirusinfected cells, and Bey et al (1993) have demonstrated that the 27-kDa protein, an α-type subunit of proteasomes, has one distinct mRNA binding domain. A widely accepted argument for a possible relationship among proteasomes and RNA is the presence of small RNA molecules in pure preparations of proteasomes (Arrigo et al, 1985;Martins de Sa et al, 1986).…”
Section: Discussionmentioning
confidence: 94%
“…The highly conserved N-terminal box found in the a-subunits of the proteasome (Zwickl et al 1992), which is believed to be involved in the formation of the external pores of the particle and in the interaction with regulatory complexes (Lupas et al 1995), is also found in the T. cruzi sequence. The proteasome motif GXXXD and the a-family motif RPXG (Bey et al 1993) are also present in TCPR29A. The C-terminal region of the T. cruzi protein is rich in charged residues, a characteristic also found in the other a6 sequences.…”
Section: Resultsmentioning
confidence: 79%
“…Prosomal P27K protein, which is not expressed in keloid fibroblasts, is involved in the regulation of cell differentiation and the cell cycle. Also, because of the proteolytic activity of this protein, it is involved in protein degradation [38, 39]. …”
Section: Discussionmentioning
confidence: 99%